Воздействие импульсов прямого тока на время жизни неосновных носителей заряда в р+–n-диоде - Kushnirenko, V. V.; Ninidze, G. K.; Pavljuk, S. P.; Savitsky, S. M.; Tretyak, O. V. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
A method is proposed for controlled modification of the lifetime of minority charge carriers in the base of a semiconductor diode crystal under the action of a short modifying current pulse, which leads to sharp non‑uniform heating of the crystal. Studies have been carried out on changes in the characteristics of industrial diode crystals KD105–KD209. The energy parameters of newly introduced recombination centers have been determined.